The Distribution and Movement of American Cockroaches in Urban Niches of New Orleans. (October 2017) - Carlson, John C.; Rabito, Felicia A.; Werthmann, Derek; Fox, Mark
American cockroaches are an important source of household allergens in tropical and semitropical climates. To determine which outdoor niches produce American cockroaches, traps were placed at 40 homes in New Orleans to collect nymphs. Nymphs were collected from the sewers, yards, and within the homes themselves. To compare sewers and yards as sources of cockroaches entering homes, adult cockroaches were collected, marked, and released into yards and sewers. No sewer-released cockroaches were collected in homes. Cockroaches released into yards were collected in the homes, suggesting that yards, rather than sewers, are a more important source niche. A field trial applying boric acid granules to the yard was performed in an effort to reduce entry of cockroaches. There was a significant reduction in the cockroach antigen collected in intervention homes compared with controls.